Glycerol on the productive performance and characteristics of the carcass and meat of goat: a meta-analysis - Vega Britez, Gustavo Daniel (2021)
The aim of the present meta-analytical study was to evaluate the effect of glycerol in the diet on the productive performance, nutrient digestibility and the characteristics of the carcass and meat of fattening goats. A systematic review was made using the Google Scholar, ScienceDirect and SciELO databases. Keywords such as crude glycerine, intake, goat, kids, carcass, meat quality were used. As inclusion criteria of the scientific articles, the presence of a control treatment (0% glycerol) and at least a percentage of glycerol in the diet, data regarding the digestibility of nutrients, productive response, characteristics of the carcass and meat and glycerol level in crude glycerin were considered in papers published between 2014 and 2019. In total, 56 articles were selected, of which 11 met the inclusion criteria. Given the heterogeneity or amplitude of the glycerol levels, the levels were grouped: 0, 1.27-4.38 and 6.40-9.60% of glycerol based on the dry matter of the diet. Normality, variance and regression analyses were performed from the data of each variable within each level of glycerol in the diet. The high variation of glycerol levels in crude glycerine was evidenced. Glycerol up to 9.60% in the diet does not compromise digestibility, consumption, main characteristics of the carcass and goat meat.